Painting in excess : Kyiv's art revival, 1985-1993 - Martynyuk, Olena (Zimmerli Art Museum, Rutgers University Press, 2021)
The upheavals of glasnost and perestroika followed by the collapse of the Soviet Union remarkably transformed the art scene in Kyiv, launching Ukrainian contemporary art as a global phenomenon. The previously calm waters of the culturally provincial capital of the Ukrainian Soviet Republic became radically stirred with new and daring art made publicly visible for the first time since the avant-garde period of the early twentieth century. As artists were freed from the dictates of the fading Communist ideology and the constraints of late socialist realism, an explosion of styles emerged, creating an effect of baroque excess. This exhibition catalogue traces and documents the diverse artistic manifestations of these transitional and exhilarating years in Kyiv while providing some historical artworks for context. Published in partnership with the Zimmerli Museum.